Distorted Dreams: Peter Ibbetson from Illustration to Adaptation - Maxime Leroy (Cahiers Victoriens et Edouardiens)
The article shows how George du Maurier’s illustrations in his novel Peter Ibbetson inspired Henry Hathaway for his 1935 film adaptation. The hypothesis is that although some visual correspondences are obvious, a change of cultural paradigm occurred. Du Maurier’s 1891 references to Butler, Laycock, Barrett, Youmans, and to the theories of the electrical body and ancestral memory, were superseded by references to Freud and psychoanalysis.